Woman Language Features in Recode World’s Technology Conference: A Sociolinguitics Studies - Deby Rahmawati; Elvi Citra resmana; Lia Maulia Indrayani (Universitas Lancang Kuning, 2019)
This research analyzes the women language features in giving public speeches in RECODE World’s Technology Conferences. The writer used Lakoff’s on Holmes (2013) theory to analyze the data. The writer applies descriptive qualitative method by Creswell (2014). Data for this reseach is women utterance during conference. Basen on theory by Lakoff, the author discover six women language features.The result of this research shown that there are six women language feature that appear, there are lexical hedges, intensifier, superpolite form, avoidance strong swear, empty adjective, and emphatic stress. Keyword: sociolinguistics, gender language, women language features.